Multicultural Readings: Product and Process - Mukundan, Jayakaran; Ting, Su Hie (Fifth National Conference on Community Languages and English for Speakers of Other Languages, 1996)
In reading classrooms, reading comprehension skills usually take priority. Teachers constantly provide comprehension exercises which reinforce skills like skimming, scanning, inferencing, predicting and vocabulary recognition. This becomes the overriding concern, so much so that the overall development of learners as readers is totally neglected. According to Muskowitz (1978), this is reflective of a dead classroom where learners are perceived as containers whose primary function is to receive and hold subject matter given by the teacher. Their understanding of the subject matter is then assessed via comprehension questions. Learners are seldom given the chance to explore their responses and feelings towards the readings. There is little scope for creative and reflective thinking.